The Application of Compulsory Bequest to Non-Muslim Heirs: A Comparative Study of Islamic Law and Jurisprudence in Indonesia - Mirza Elmy Safira; Alief Akbar Musaddad; Bambang Supriadi; Hamzah Mardiansyah; Mawardi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The application of wasiat wajibah (compulsory will) is a significant issue within inheritance law in Indonesia, particularly regarding non-Muslim heirs who inherit from Muslim relatives. In Islamic law, wasiat wajibah refers to the entitlement given to heirs who are excluded from inheritance based on the faraid rules, with the intention of promoting fairness. This research aims to evaluate the application of wasiat wajibah for non-Muslim heirs, through a comparative analysis between Islamic law and the current jurisprudence in Indonesia. The methodology applied is a normative approach, focusing on the analysis of relevant legislation and judicial precedents. The discussion covers the concept of wasiat wajibah in Islamic law, its implications for non-Muslim heirs, and an evaluation of how it is implemented within the Indonesian legal framework. The results are expected to enhance the understanding of the implementation of wasiat wajibah in Indonesia’s multi-religious society.